Clinical Diagnosis: When Is It Not Inflammatory Bowel Disease?. (1st November 1990) - Williams, CN
Abstract : Three situations mimic ulcerative colitis. First, in homosexual men, acute self-limited colitis due to campylobacter, salmonella or shigella is seen. Neisseria gonorrhea, herpes simplex, Chlamydia trachomatis and Entamoeba histolytica or a combination of these may also be present. The second setting is that of acquired immune deficiency syndrome (AIDS), where opportunistic infections, cytomegalovirus, cryptosporidium, Salmonella typhimurium and Escherichiacoli 0157: H7 may cause diagnostic difficulty. The third situation is when patients have recently returned from or are in an endemic area for infectious diarrhea. This particularly affects the elderly, where salmonella, E coli 0157:H7, shigellosis and, increasingly, pseudomembranous colitis secondary to cycotoxin from Clostridium difficile, occur. The differential diagnoses for Crohn's disease include such disparate conditions as solitary rectal ulcer in females, and ischemic change in the elderly, which usually involves the splenic flexure area of the colon, but may also involve the recrosigmoid area. When a mass is present in the right lower quadrant, the differential diagnosis also includes local abscess formation from a perforated appendix or foreign body, tuberculosis and carcinoma. In the immunocompromised patient, Mycobacterium avium-intracellulare infection and Kaposi's sarcoma may mimic inflammatory bowel disease. Yersinia enterocolitica is becoming increasingly recognized as a cause of acute enteritis, predominantly in the ileum, often with coexistent mesenteric adenitis. Drugs may also cause diagnostic confusion. The one most recognized is antibiotic-associated pseudomembranous colitis. However, cleansing soapsuds, Fleet (Frosst) and bisacodyl enemas, methyldopa and Myochrysine (Rhone-Poulenc) may also cause colitis. Nonsteroidal anti-inflammatory agents may produce ileal ulceration and a clinical and radiological picture resembling Crohn's disease. Potassium chloride also causes discrete ileal ulcers. Five case reports arc presented to illustrate these diagnostic difficulties.